Contribuições sobre a gestão territorial da (des)proteção social dos povos indígenas Potiguara do litoral norte da Paraíba, Brasil - Silva, Taiane Macêdo (2021)
The present dissertation - which is part of the thematic field of the relations between Social Protection, Territory and the Indigenous Question - aims to elucidate the debate on the territorial management of Social (Dis) Protection of indigenous peoples from the north coast of Paraíba. It seeks to contribute to the strict sense debate on the territorial management of the social (dis) protection of indigenous peoples in the northern region of Paraíba. Specifically, it aimed to problematize the indigenous question in Brazil, based on historicity, rescuing the processes of exposure, struggles, resistance and the State's responses to this problem; talk about noncontributory protection in Brazil, based on the social assistance policy; characterize the Potiguara indigenous territory on the northern coast of Paraíba and characterize the SUAS socio-assistance network in relation to its coverage in the Potiguara indigenous territory on the northern coast of Paraíba.With a qualitative approach, this exploratory investigative study was developed in three phases: the first, bibliographic survey; the second with research through official secondary data, collected on online government platforms, laws and regulations, and the third empirical, with the application of semi-structured interviews with workers from the SUAS service network in their area of coverage in the region. Finally, with the categories of analyzes were worked from socio-territorial indicators elucidated through the secondary data collected and in the light of the perception of SUAS workers in Baía da Traição / PB. The results allow to identify the configuration of the socio-assistance network and some socio- territorial indicators of the Potiguara indigenous people from the North Coast of Paraíba, specifically the potential and weaknesses of the socio-assistance network, in a specific way, as configured to the social (dis) protection of the Potiguara indigenous in their territories. the North Coast. In the analytical study, the challenges posed to the management of social protection in the Potiguara territories are highlighted; the dissonances between what is provided for in the regulations regarding equity in serving traditional peoples, in rural and urban areas; the dilemmas between the limits and possibilities for the management of SUAS social assistance services, and also a “deficit” in the demand and supply relationship of the public equipment network and services in relation to the training and conditions of its workers who work in the protection management basic and special social protection in indigenous territories. It is evident, therefore, the need to move forward in improving the challenging offer to strengthen the social protection of the Potiguara, in view of the sine qua non relationship between Social Protection and Indigenous Territory.